Post Abortion Contraception Model: A Comprehensive Package for Improving Safe Abortion Care in Developing Countries - Yao Gbagbo Fred (Journal of Family Medicine, 2018)
Background: Despite liberal abortion laws and wide availability of contraceptives in Ghana, declining Post Abortion Contraception remains a public health challenge due to early unplanned pregnancies and recurrent abortions. The development of this model was therefore to address challenges of low contraception following induced abortion in health facilities within the capital city of Ghana. Method: The development of this model was an outcome of a nested study title: ‘decision making for induced abortion in Accra metropolis, Ghana’ in 2014. This model was piloted for four years using Marie Stopes, Ipas and Ghana Health Service trained abortion providers with family planning skills in one hundred purposively selected health facilities comprising 90 private and 10 Non-Governmental Organization mandated by law to provide safe abortion care services in the capital city of Ghana. The model mainly focused on contraceptive products, pricing, placement, promotion and people. Results: There was an increase (90% average) in Post Abortion Contraception across the selected facilities following the intervention using the model. Conclusion: The study concludes that an integration of products, pricing, placement, promotion and people with options counselling prior to an induced abortion are key considerations for an improved post abortion contraception uptake in developing countries.
Keywords: Post Abortion Contraception